2010
DOI: 10.3109/15563650.2010.498790
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylformamide metabolism following self-harm using a veterinary euthanasia product

Abstract: While both patients had a favorable outcome, there is no clear evidence that NAC could directly influence NMF and AMCC excretion. Further investigations of NMF and AMCC excretion, with and without NAC, would be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Following absorption, DMF is evenly distributed, metabolized mainly in the liver, and rapidly excreted in the form of metabolites through urine (Fig. 1) [7,10,27-31]. A series of studies have shown that DMF is N -methylated by microsomal enzymes in the liver, and that cytochrome P450s plays a role in the biotransformation of DMF [27,32-34].…”
Section: A Generalized Pathway Of Dmf Metabolism In the Livermentioning
confidence: 99%
See 3 more Smart Citations
“…Following absorption, DMF is evenly distributed, metabolized mainly in the liver, and rapidly excreted in the form of metabolites through urine (Fig. 1) [7,10,27-31]. A series of studies have shown that DMF is N -methylated by microsomal enzymes in the liver, and that cytochrome P450s plays a role in the biotransformation of DMF [27,32-34].…”
Section: A Generalized Pathway Of Dmf Metabolism In the Livermentioning
confidence: 99%
“…1) [7,10,27-31]. A series of studies have shown that DMF is N -methylated by microsomal enzymes in the liver, and that cytochrome P450s plays a role in the biotransformation of DMF [27,32-34]. Thus, the toxic effect elicited by DMF exposure is much more severe in the liver than in any other organ, presumably because its metabolism is mainly catalyzed by hepatic cytochrome P450s [27,32-34].…”
Section: A Generalized Pathway Of Dmf Metabolism In the Livermentioning
confidence: 99%
See 2 more Smart Citations
“…It is mainly susceptible to chemical injury due to its extensive metabolic capacity and cellular heterogeneity. The major target organ of DMF toxicity is the liver, due to its high content of cytochrome P-450 [1] DMF metabolism takes place in the liver, and excreted as metabolites through urine (Hantson et al, 2010). Previous studies have revealed that DMF is N-methylated by the liver microsomal enzymes, and cytochrome P-450 involves in the biotransformation [2].…”
Section: Introductionmentioning
confidence: 99%